RELATIONSHIP OF RISK FACTORS WITH HISTOPATHOLOGICAL TYPES IN CERVICAL CANCER PATIENTS IN DR SOETOMO HOSPITAL - Anggray Puspasari; Pungky Mulawardhana; ,Nila Kurniasari (SEAJOM: The Southeast Asia Journal of Midwifery, 2021)
Cervical cancer is a process of changing into malignancy in the cervix. Based on studies and previous research, cervical cancer is the third female cancer in terms of incidence (527,600 new cases) and mortality (265,700 deaths) in the world. Cervical cancer has histotopathological types in the form of squamous cell carcinoma, adenocarcinoma, and other types. This study aimed to analyze the relationship of risk factors with histopathological types in cervical cancer patients in Dr. Soetomo Hospital. Method: This analytical descriptive study used a cross sectional research design. The number of samples were 300 patients collected by total sampling. Independent variables were risk factors including age, marital age, parity, smoking, oral contraceptives, and education while dependent variables were histopathological types including squamous cell carcinoma, adenocarcinoma, and other types. Instruments used documentation. Data analysis used chi square, fisher and contingency coefficient tests. Results: There was a relationship of cervical cancer risk factors of age to histopathological type (p= 0.000 and contingency coefficient = 0.170) and no relationship of risk factors to number of parity (p= 0.321 and contingency coefficient = 1000 0.064 ), marriage age (p = 0.720 and contingency cofience = 0.038), smoking (p = 0.711 and contingency cofience = 0.036), oral contraceptive (p = 0.655 and contingency comfience = 0.042), education (p = 0.744 and contingency co-efficiency = 0.089) to histopathological type. Conclusion: There is a relationship between risk factors and histopathological types in cervical cancer patients at Oncology Polyclinic at Dr Soetomo Hospital of Surabaya.